THE INFLUENCE OF MICRO FINANCING AND BUSINESS ASSISTANCE ON THE DEVELOPMENT OF CLIENTS' BUSINESSES AT PT MITRA BISNIS KELUARGA VENTURA, TANAH TINGGI BRANCH, TANGERANG CITY - Diansyah, Diansyah; Aslawiyah, Siti Rabiaatul (STKIP Persada Khatulistiwa Sintang, 2024)
PT MBKV (Mitra Bisnis Keluarga Ventura) is a non-bank private financial institution that engages in microfinance activities. This study aims to ascertain whether microfinance and business assistance exert a combined and partial influence on the business development of customers of PT Mitra Bisnis Keluarga Ventura Tanah Tinggi Branch in Tangerang City. The population comprised 203 customers, while the sample size was limited to 135. The data collection process involved the use of observation, questionnaires, and interviews. The data analysis technique employs instrument testing and hypothesis testing. The independent variable comprises microfinance and business assistance, while the dependent variable is business development. A multiple linear regression analysis was conducted to test the effect of each independent variable on the dependent variable. The results of data processing through SPSS 27 indicate that microfinance and business assistance exert a significant influence on the business development of customers of PT Mitra Bisnis Keluarga Ventura Tanah Tinggi Branch in Tangerang City. The influence of microfinance and business assistance on business development is significant, with a magnitude of 47.3%. Furthermore, the provision of microfinance and effective business assistance can facilitate continuous business development, thereby achieving optimal results.